Gender Differences in Giving in the Dictator Game: The Role of Reluctant Altruism - Klinowski-Gomez, D (SPRINGER, 2018)
The Dictator Game has been a helpful tool to study whether men or women are more generous. But recent work suggests that motivations other than generosity also influence behavior in this game. Image concerns and expectations management may cause dictators to "give reluctantly"; that is, to share money with the recipient if asked to, but to renege on their gifts if they can do so without being detected. We provide evidence from two separate experiments that females are more likely than males to give reluctantly in the Dictator Game. After accounting for retraction of gifts, males and females transfer similar amounts to the recipient in expectation. The results suggest that gender differences in non-payoff-related motivations may play a role in producing gender differences in giving in the Dictator Game.